Cellular plasticity and myeloid inflammation in the adult brain are independent of the transcriptional modulator DREAM - Masanetz, Rebecca Katharina; Baum, Wolfgang; Schett, Georg; Winkler, Jürgen; Süß, Patrick (Neuroscience Letters, 2023)
The downstream regulatory element antagonist modulator (DREAM) modulates ion channel function and gene transcription. Functionally, DREAM is implicated in physiological and pathological processes including cell proliferation, inflammation, and nociception. Despite its multiple functions and robust expression in forebrain tissue, neurons and glial cells, the role of DREAM in regard to cellular plasticity and tumor necrosis factor (TNF)-mediated inflammation is largely unexplored. Here, we demonstrate that adult hippocampal neurogenesis as well as the density and plasticity of glial cells in the hippocampus and thalamus are independent of the presence of DREAM. Further, DREAM deletion does not alter the regional myeloid response and inflammatory gene expression induced by chronic peripheral inflammation in mice overexpressing human TNF. Our data suggest that despite their highly dynamic regulation, neural cell plasticity and adult neurogenesis in the hippocampus do not depend on the multifunctional protein DREAM. Furthermore, TNF-mediated myeloid inflammation in the brain persists in the absence of DREAM.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Adult hippocampal neurogenesis; DREAM; Glia; Neuroinflammation; Pain; Proliferation